The Rainbow Magic collection : volume 2: books #5-7 - Meadows, Daisy; Ripper, Georgie (New York : Scholastic INC, 2008)
"Fairyland is home to seven colorful sisters. Together, they are the Rainbow fairies! They keep Fairyland dazzling and bright. But when evil Jack Frost sends them far away, the sisters are in big trouble. If they don't return soon, Fairyland is doomed to be gray forever!"-- Cover back.
Sky the blue fairy -- Inky the Indigo fairy -- Heather the violet fairy -- Hannah the happily ever after fairy.
"Plus, an all-new bonus story!"--Cover.
"Little Apple."
Keywords: Fairies -- Fiction; Color -- Fiction